2018
DOI: 10.15406/emij.2018.06.00148
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Carcinoma - A 25 Years Tertiary Centre Experience and Short Review of the Literature

Abstract: We performed an informatics search of the medical registers of our centre (filtered by age -over 18-years-old) for the diagnosis codes 'adrenal neoplasia' and 'adrenocortical carcinoma', and Review ArticleEndocrinol Metab Int J 2018, 6(1): 00148 AbstractPurpose: Adrenocortical carcinoma (ACC) is an uncommon and aggressive malignancy. We aimed to investigate the clinical and pathological findings of ACC diagnosed/treated in our hospital from January/1988 to January/2013.Methods: Analysis of presentation, imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Moreover, tumor volume > 500 cm 3 was related with shorter survival rate in the multivariable analysis. In line with previous reports [27,28], we found that most of the ACC cases were women at forthfifth decade of life, with stage II (ENSAT criteria) and located on the left, albeit not all studies agree with the left sided preponderance [29]. We also observed a trend for positive correlation between tumor size (volume and diameter) and left localization.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, tumor volume > 500 cm 3 was related with shorter survival rate in the multivariable analysis. In line with previous reports [27,28], we found that most of the ACC cases were women at forthfifth decade of life, with stage II (ENSAT criteria) and located on the left, albeit not all studies agree with the left sided preponderance [29]. We also observed a trend for positive correlation between tumor size (volume and diameter) and left localization.…”
Section: Discussionsupporting
confidence: 91%
“…The tumor stage is also associated with OS, with worse outcome in higher stages. 40 In the patients at stage II—the majority of our cohort, tumor size equal or superior to 10 cm, showed an effect on OS in multivariate analysis, with a high hazard ratio. This finding supports that simply diagnosing ACC is not enough for proper patient management and that more data should be integrated.…”
Section: Discussionmentioning
confidence: 73%
“…2,3 The clinical presentation can be varied and related to either hormone excess (cushiongoid features, hirsutism, virilization) or non specific symptomatology related to tumour growth (pain, abdominal fullness, general malaise). 4 Most adrenal cortical carcinomas occur sporadically but rarely its association with hereditary syndromes like Li Fraumeni syndrome, Beckwith-Weidmann syndrome is reported in pediatric population, while in adults higher prevalence in association with Lynch syndrome, Multiple endocrine neoplasia type 1 (MEN 1) and Type 1 neurofibromatosis is well documented. 5 Although radiological and histopathological characterization of adrenal cortical neoplasm as adenoma or carcinoma is quite straightforward, sometimes a benign tumour showing haemorrhage and revascularization on imaging and intermediate histology can pose a challenge.…”
Section: Introductionmentioning
confidence: 99%